Strategies in Applying the Religious Character of Students to Distance Learning - Aldiyah Mellawati (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to determine the strategy of SMP Muhammadiyah 5 Tulangan in applying the religious character of students in distance learning. This study uses descriptive qualitative research methods. The data collection technique in this study was through interviews, documentation and observation, while the triangulation used in this study was technical triangulation. In online learning, SMP Muhammadiyah 5 Tulangan has implemented an online learning strategy using the help of technology and communication tools. Religious character is needed by students in dealing with changing times and moral degradation. Kemuhammadiyahan lessons are considered strategic to be disseminated to every student in Muhammadiyah schools. Morning activity is an activity that is routinely carried out every morning by reading the Qur'an or usually referred to as the morning prayer and dhuha prayer as an effort to strengthen the value of the religious character of the students of SMP Muhammadiyah 5 Tulangan.